Method for in situ polypyrrole coating, and the example of its use for functionalization of polyurethane anisotropic electrospun mats - Mahelová, Leona; Slobodian, Petr; Kocourková, Karolína; Minařík, Antonín; Moučka, Robert; Trchová, Miroslava; Martínková, Martina; Skopalová, Kateřina; Víchová, Zdenka; Kašpárková, Věra; Humpolíček, Petr (Heliyon, 2024)
The in situ coating of polymer substrate with polypyrrole, described herein with detailed know-how, represents a novel technique of surface functionalization. The choice of oxidizing agent and the polymerization time both affect the properties of the thin polypyrrole layer. The specific conductivity, free surface energy, thickness, topography, and FTIR spectra of polypyrrole layer were determined. The conductive coatings were further used to functionalize both isotropic and anisotropic electrospun polyurethane nanofibrous mats to show their applicability and study the bioactive effect of both the anisotropy and conductivity together. The morphology of composites was studied by means of atomic force microscopy and scanning electron microscopy. A complex cytocompatibility study was performed, including determining cytotoxicity by optical and fluorescence microscopy, the advanced qualification of cell morphology by cell-image analysis, and a study of stem cell behavior. The results clearly showed the significant impact of substrate modification on cells, especially on fibroblasts while the embryonic stem cells were less affected. This study shows not only the effective way to prepare a thin conducting layer based on polypyrrole but also demonstrates its importance for the fabrication of smart biomaterials.
Keywords: Conductivity; Anisotropy; Stem cells; Coating; Image analysis